Potassium disorder in the defect pyrochlore KSbTeO6: A neutron diffraction study - Alonso, José Antonio (2017)
KSbTeO6 defect pyrochlore has been prepared from K2C2O4, Sb2O3, and 15% excess TeO2 by solid-state reaction at 850 °C. Direct methods implemented in the software EXPO2013 allowed establishing the basic structural framework. This was followed by a combined Rietveld refinement from X-ray powder diffraction (XRD) and neutron powder diffraction (NPD) data, which unveiled additional structural features. KSbTeO6 is cubic, a = 10.1226(7) Å, space group Fd3m, Z = 8 and it is made of a mainly covalent framework of corner-sharing (Sb,Te)O6 octahedra, with weakly bonded K+ ions located within large cages. The large K-O distances, 3.05(3)–3.07(3) Å, and quite large anisotropic atomic displacement parameters account for the easiness of K+ exchange for other cations of technological importance.